G111(P) The Role of Modafinil in IMproving Motor Function in Cerebral Palsy: A Case Study. (4th June 2013) - Crouchman, M; Greenberg, H; Hughes, R
Abstract : Background: An American study showing improved Gross Motor Function (GMF) in cerebral palsy (CP) attributed this to a direct action on spasticity of modafinil, a drug used to treat Attention Deficit/Hyperactivity Disorder (ADHD). There is no other evidence that modafinil reduces spasticity. Purpose: To clarify modafinil's mode of action. Methods: Our subject was a 9 year old girl with spastic diplegia, seen previously by a number of paediatricians. Following clinical assessment the GMF score and the modified Connor score for ADHD were recorded. These were repeated after one month's treatment with modafinil. Results: Her initial Connor score was 21/30 (very high), and fell to 5/30. Her GMF rose from 28 (25% of norm) to 139 (49.8%). A detailed history from her mother and clinical examination suggested ADHD. During treatment she had a growth spurt, and after one month her spasticity had increased and her gait deteriorated. However, she had better control of her walking aid, she achieved alternation of her feet on stair climbing and improved ability to handle cutlery, she was able to undress herself for the first time, her stamina and tolerance of physiotherapy improved and her speech and writing became clearer. There were also marked improvements in cognitive and social functioning; she gained 2 levels in reading and read independently for the first time, she was less emotionally labile, she slept better and became more appropriate in behaviour and interactions. She expressed pleasure in these gains. Conclusions: Motor improvement occurred despite increased spasticity. It was associated with reduction in both distractibility and excessive movements, both symptomatic of ADHD, and it is probable that treatment for this condition improved her motor function. Methylphenidate and other drugs used to treat ADHD are likely to produce similar benefits. ADHD is common in cerebral palsy, particularly in diplegia associated with prematurity, but rarely diagnosed. Increased awareness and treatment of comorbid ADHD may make the difference between achieving and maintaining walking or becoming wheelchair dependent, with important implications for quality of life and life expectancy.